Super-capacitive behavior of carbon nano tube doped 11-(4-cyanobiphenyl-4-oxy) undecan-1-ol - Ozdemir, Z. Guven; Canli, N. Yilmaz; Senkal, B. F.; Gursel, Y.; Okutan, M. (ELSEVIER, 2015)
In this study, the influence of carbon nano tube (CNT) doping on ac conductivity mechanism and electronic properties of the 11-(4-cyanobiphenyl-4-oxy) undecan-1-ol (LC11) has been analyzed by means of dielectric and impedance spectroscopy measurements. It has been revealed that CNT doping enhances the capacitive behavior that results a super-capacitor ability for the low frequency region up to 100 Hz. From this point of view, CNT doped LC11 may be proposed as a new composite material for super-capacitor applications. In addition, it has been determined that the conductivity mechanism changes from Nearly Constant Loss model to Super Linear Power Law behavior by adding CNT for the low frequency region. For the high frequency region, the conductivity mechanism approaches to Correlated Barrier Hopping mechanism by doping CNT to LC system. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Composite material; Liquid crystal; Impedance spectroscopy; Super-capacitor; PRINCIPLES; NANOTUBES; FILMS; Chemistry; Physics